American military history : a very short introduction - Glatthaar, Joseph T., 1956- (New York, NY : Oxford University Press, 2020)
"American Military History: A Very Short Introduction outlines the forces shaping the American military for the past 400 years. Since the colonial period, the United States has struggled to balance standing armed forces with citizen soldiers and sailors. Technological developments and two world wars forced the military to embrace professionalism and its increased obligations. The United States emerged from World War II in a strong position but failed to recognize the limits of its power, a legacy that some might say continues. Recent wars highlight some of the problems of a volunteer-dominated force. To succeed, the American military needs improved communication, understanding, and support"--
Citizen soldier and sailor vs. standing armed forces -- The struggle for military professionalism -- Technology, mechanization, and the world wars -- The limits of power -- Conclusion: The armed forces and perennial problems
"Published in hardcover as The American Military in 2018."
Includes bibliographical references and index.
Keywords: United States -- Armed Forces -- History; United States -- History, Military